Rare spider species (Araneae) of protected steppe areas of the Kharkiv Region (Ukraine) - Polchaninova, N. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2019)
A total of 426 spider species is known in the fauna of the Kharkiv Region. Of these, 32 species may be considered rare and/or vulnarable. The largest steppe areas in the Kharkiv Region are protected in the National Nature Park “Dvorichanskyi” and the Regional Landscape Park “Velykoburlutskyi Steppe”. The former hosts 11 rare spider species, the latter 13 species, and eight species occur in both Parks. For the species Lathys heterophthalma, Trachyzelotes lyonneti, Russocampus polchaninovaе, and Euryopis laeta it is the only valid record from Ukraine; for Pardosa maisa, Dipoena coracina, and Talavera aperta, maximun two or three localities are known. Titanoeca veteranica and Altella hungarica are the new records to the Kharkiv Region. Two species are extremely rare, Altella hungarica has been found in only seven localities in Europe, and Russocampus polchaninovae in four localities. Northern boundaries of the geographic ranges of Civizelotes pygmaeus, Gnaphosa dolosa, Xysticus marmoratus, X. mongolicus, and the southern boundary of Gnaphosa lugubris run through the Kharkiv Region. On the edges of their areas, these species become habitat specialists and occur only in steppes and/or dry meadows. Xyticus mongolicus inhabits sandy and chalky steppes with sparse vegetation. Gnaphosa taurica has high ecological plasticity in the steppe zone, while in the forest-steppe, it is limited with chalk and limestone outcrops. Some species like Gnaphosa lugubris, G. licenti, G. taurica, Zora pardalis and Eresus kollari, were abundant in our samplings while 19 species were found as singletons. G. taurica, and E. kollari preferred chalky slopes, G. licenti both chalky slopes and top of a southern ungrazed slope, G. lugubris dominated on all slopes in the Velykoburlutskyi Steppe, while Z. pardalis was the most abundant in ungrazed gully bottoms in both Parks. Being not numerous, Altella hungarica, Euryopis laeta, Civizelotes pygmaeus and Drassyllus vinealis occurred annually in the same habitats that may indicate stability of their populations. Given their habitat specificity, even numerous species became vulnerable under the threat of anthropogenic transformation of natural ecosystems. The only way to protect them is to preserve their habitats.